Fingerprint analysis for the determination of hand origin (right/left) using the axis slant in whorl patterns - Neeti Kapoor; Ashish Badiye; Swati Dubey Mishra (Oxford University Press, 2020)
Fingerprints are frequently encountered during both civil and criminal investigations. Fingerprints possess numerous characteristics that assist with personal identification. Determining the hand of origin (right or left) for an individual fingerprint would help reduce investigation time and potentially eliminate certain suspects. In this study, we collected a total of 2 900 single digit fingerprints from 290 individuals, and the whorl axis slant was examined in the 743 whorl pattern fingerprints (385 from the right hand and 358 from the left hand). A slant towards the right side was present in 81.82% of samples from the right hand, while a slant towards the left side was observed in 80.73% of samples from the left hand. After applying a chi-square test to the dataset, the results were found to be statistically significant for the determination of hand origin. Our results suggest that the whorl axis slant in a fingerprint is indicative of hand origin (right or left).Key points Single digit fingerprints with whorl pattern were analyzed. Whorl "axis slant" was used to determine the hand origin. Right axis slant would indicate the right hand of the print. Left axis slant would indicate the left hand of the print.